Types and cognitive levels of questions asked by secondary agricultural science teachers - Abdul Latir, Siti Shuhaidah; Whittington, M. Susie (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Higher level cognitive questions such as open-ended and rhetorical questions aid teachers in exploring students’ ideas (Ewing, 2006). Asking a wider range of questions requires students to analyze, evaluate, and develop conceptual and procedural knowledge (Tofade et al., 2013). The purpose of this study was to identify the types and cognitive levels of questions used by first-time secondary agricultural science teachers in the Curriculum for Agricultural Science Education (CASE) program in Ohio. Participants in this study implemented inquiry-based instructional approaches in their classrooms and the researchers intended to describe the type and cognitive level of questions the teachers asked. Teachers’ questions were categorized by type and cognitive level. Question types were categorized using the Teacher Question Type Frequency Form. Question types described in this study include open, closed, managerial, and rhetorical questions. The cognitive level of questions was categorized using Bloom’s Taxonomy (Bloom et al., 1956), which includes the categories of knowledge, comprehension, application, analysis, synthesis, and evaluation. Closed-type questions were found to be the most common (37%) type of questions asked by participating teachers during implementation of inquiry-based instructional techniques. Meanwhile, nearly 59 percent of the questions asked by teachers were at the lowest cognitive level (knowledge level) of Bloom’s Taxonomy. Secondary agricultural science teachers asked mostly closed-type questions during their implementation of inquiry-based instruction, while analysis-level questions were the least utilized category (9.33%). Overall, teachers asked a limited number of higher cognitive level questions during observed class sessions. Secondary agricultural science teachers are recommended to consider the cognition level of questions they develop for classroom discussion. Teachers should also consider student needs and prior knowledge when formulating questions and learning objectives. When teachers understand and apply the best strategies of questioning to their teaching, students will learn at higher levels of thought.